Bioengineering functional human sphincteric and non-sphincteric gastrointestinal smooth muscle constructs - Rego, Stephen L (Methods, 2015)
Digestion and motility of luminal content through the gastrointestinal (GI) tract are achieved by cooperation between distinct cell types. Much of the 3 dimensional (3D) in vitro modeling used to study the GI physiology and disease focus solely on epithelial cells and not smooth muscle cells (SMCs). SMCs of the gut function either to propel and mix luminal contents (phasic; non-sphincteric) or to act as barriers to prevent the movement of luminal materials (tonic; sphincteric). Motility disorders including pyloric stenosis and chronic intestinal pseudoobstruction (CIPO) affect sphincteric and non-sphincteric SMCs, respectively. Bioengineering offers a useful tool to develop functional GI tissue mimics that possess similar characteristics to native tissue. The objective of this study was to bioengineer 3D human pyloric sphincter and small intestinal (SI) constructs in vitro that recapitulate the contractile phenotypes of sphincteric and non-sphincteric human GI SMCs. Bioengineered 3D human pylorus and circular SI SMC constructs were developed and displayed a contractile phenotype. Constructs composed of human pylorus SMCs displayed tonic SMC characteristics, including generation of basal tone, at higher levels than SI SMC constructs which is similar to what is seen in native tissue. Both constructs contracted in response to potassium chloride (KCl) and acetylcholine (ACh) and relaxed in response to vasoactive intestinal peptide (VIP). These studies provide the first bioengineered human pylorus constructs that maintain a sphincteric phenotype. These bioengineered constructs provide appropriate models to study motility disorders of the gut or replacement tissues for various GI organs.